2015
DOI: 10.3329/bjar.v40i1.23752
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield, nutrient balance and economics of T. Aman rice cultivation as influenced by nutrients management

Abstract: A field experiment was conducted at Regional Wheat Research Centre of the Bangladesh Agricultural Research Institute, Joydebpur, Gazipur, Bangladesh during 2007 and 2008. The objectives were to find out the optimum nutrient management practice for grain yield, nutrient balance and economics of T. Aman rice. Twelve nutrient management treatments (with and without CRI) were tested in RCBD with 3 replications. Treatments were T1=HYG (0-80-16- 44-12-2-0), T2=MYG (0-56-12-32-8-1.5-0), T3=IPNS (5000-65-13-32-9-2-0),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
4
1
0
Order By: Relevance
“…Other studies have also showed positive balance of Zn and B in maize-mungbean-rice system when it was added [21]. Similar results corroborated by Jahan et al [41] in a monocrop cultivation of T. aman rice where -0.08 to -0.31 kg Zn ha -1 yr -1 was in control and farmers practice and positive balance (1.12 to 1.61 kg Zn ha -1 yr -1…”
Section: Discussionsupporting
confidence: 79%
“…Other studies have also showed positive balance of Zn and B in maize-mungbean-rice system when it was added [21]. Similar results corroborated by Jahan et al [41] in a monocrop cultivation of T. aman rice where -0.08 to -0.31 kg Zn ha -1 yr -1 was in control and farmers practice and positive balance (1.12 to 1.61 kg Zn ha -1 yr -1…”
Section: Discussionsupporting
confidence: 79%
“…The soil test based fertilizer treatment (T4) showed the significantly higher nutrients uptake by wheat in both the years. Similar results were found by Jahan et al (2015a). The second highest uptake was observed in T3 which was followed by T2.…”
Section: Nutrient Uptakesupporting
confidence: 88%
“…So, the AEZ (T 3 ) and soil test based treatments (T 4 ) showed positive balance of Zn. Similar results corroborated by Jahan et al (2015b) in a monocrop cultivation of T. aman rice where -0.08 to -0.31 kg Zn ha -1 yr -1 was in control and farmers practice and positive balance (1.12 to 1.61 kg Zn ha -1 yr -1 ) was in AEZ and STB treatment. Deficiency detection of Zn in mustard, mungbean and T. aman rice in all treatments suggested for application of Zn fertilizer or further monitoring (Bell & Kovar, 2000;Kalra, 1998).…”
Section: Discussionsupporting
confidence: 75%